Lactate’s impact on immune cells in sepsis: unraveling the complex interplay - Zhang, Tao; Chen, Linjian; Kueth, Gatkek; Shao, Emily; Wang, Xiaohui; Ha, Tuanzhu; Williams, David L.; Li, Chuanfu; Fan, Min; Yang, Kun (Frontiers in Immunology, 2024)
Lactate significantly impacts immune cell function in sepsis and septic shock, transcending its traditional view as just a metabolic byproduct. This review summarizes the role of lactate as a biomarker and its influence on immune cell dynamics, emphasizing its critical role in modulating immune responses during sepsis.The interaction between lactate and immune cells is central to understanding sepsisassociated immune dysregulation, offering insights that can guide future research and improve therapeutic strategies to enhance patient outcomes.